Pengaruh Sales Growth, Capital Intensity Dan Corporation Risk Terhadap Tax Avoidance - Ilma Ilhamda Azzahra; Eko Sasongko Priyadi (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine the effect of Sales Growth, Capital Intensity and Corporation Risk on Tax Avoidance. The research method uses quantitative research with the independent variables used in this study are Sales Growth, Capital Intensity and Corporation Risk. Meanwhile, the dependent variable is Tax Avoidance which is measured by the Effective Tax Rate (ETR). The data used in this study are secondary data, namely data obtained from the annual financial reports of companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period obtained through the idx website. The population in this study was 65 Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange. The sample selection technique used purposive sampling, 16 companies were obtained as samples. The analysis technique used is multiple linear regression with the e-views version 12 tool. The results of the study show that partially the Sales Growth and Corporation Risk variables have an effect on Tax Avoidance. While Capital Intensity has no effect on Tax Avoidance. The variables Sales Growth, Capital Intensity and Corporation Risk simultaneously have an effect on Tax Avoidance.